Protocol to examine murine visceral adipose tissue immune cells using fluorescence-based flow cytometry - Anna Carey; Christina D. Camell (STAR Protocols, 2024)
Summary: Adipose tissue immune cells are heterogeneous and dynamic, alter metabolism, and drive immune responses. Here, we present a protocol for assessment and characterization of murine adipose tissue immune cells using fluorescence-based flow cytometry and sorting into pure populations. We describe steps for isolation of the stromovascular fraction, antibody staining, and data collection by flow cytometry. We also discuss common issues and troubleshooting steps.For complete details on the use and execution of this protocol, please refer to Carey et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.